Pregnancy Following Recent Radioactive Iodine Ablation in Thyroid Cancer Patient A Case Report - Robert Dwitama Adiwinoto; Soebagijo Adi Soelistijo; Hermina Novida; Agung Pranoto (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Well-differentiated thyroid carcinoma (DTC) is common among females of reproductive age. Pregnancy is associated with hormonal (TSH and HCG) and metabolic changes that might affect the thyroid gland. Informationregarding the outcome of babies born to mothers who have recently undergone radioactive Iodine-131 ablation (RAI) is scarce. A 24-year-old pregnant woman with a history of thyroid cancer was consulted by the obstetrics and gynecology for further evaluation. She complained of a lump under the left jaw, and a thyroid nodule was found from further examination. Postoperative pathology of the right thyroid tissue revealed follicular and solid variant papillary thyroid carcinoma. Postoperative Thyroglobulin (Tg) level before ablation was 16.14 ng/mL. Ablation with Iodine-131 of 100 mCi was performed. Whole-body scintigraphy (WBS) indicated remaining functional thyroid tissue in the right thyroid field and thyroid tissue metastases in the left supraclavicular area. The patient waspregnant 3 months after the radioablation. Fetomaternal examination results 6 months pregnancy revealed fetal biometry according to gestational age (31 – 32 weeks) with an estimated fetal weight of 1787 grams and fetal doppler was normal. The patient is treated with levothyroxine 125 μ g once daily, folic acid 400 μ g twice daily, calcium lactate twice daily, and aspirin 80 mg once daily. The TSH level was 0.01 (0.55 – 4.78) μ IU/mL and the fT4 was 1.14 (0.7 – 1.48) ng/dL. The latest thyroid ultrasound indicated no discrete mass in the thyroid fossa and non-specific lymphadenopathies. The baby was born normally, weighed 2680 grams, with normal thyroid function tests (neonatal TSH 1.02 μ IU/mL, fT4 2.6 ng/dL).